Molecular dynamics simulations of 〈1010〉/ψ tilt grain boundaries in ice - Di Prinzio, Carlos Leonardo (2016)
In this paper, molecular dynamics simulations (MDS) of 〈1010〉/ψ symmetric tilt ice grain boundaries are presented. The MDS were carried out using the GROMACS v4.5.5 program, and the water molecules were described using the TIP5P-Ew model. The grain boundary energies, γgb, relative to those of the surface free energies, γs, were obtained as a function of the misorientation angle Ψ, and compared with the γgb/γs values experimentally obtained. The results show a good correspondence between the experimental and simulated γgb/γs values. The planar density of coincidence sites at the grain boundary planes, Γ, was obtained as a function of ψ. The Γ values were compared with the simulated values and a relation between the minimum of the simulated γgb/γs values and the maximum of the Γ values was observed, suggesting that the CSL theory is a good starting point to detect low energy ice GBs.